Status of Sanitation in the Rural Areas of a Health Unit Dis-trict, Tamil Nadu, India - Renuka Prithviraj; P Sivaprakasam; C Mahendran; Prasan Norman; K R Pandyan; Balasubramaniam (Medsci Publications, 2017)
Background: Sanitation is the key to better health. Even towards the end of the millennium development goal era, provision of sanitation still continues to be a challenge especially in rural areas. Objectives: The present study was undertaken to describe the availability and utility of sanitary latrines in study population and to assess knowledge / practice of households about use of latrines. Materials and Methods: This cross-sectional study was carried out in Cheyyar taluk of Tamil Nadu which comprised of three blocks. Stratified random sampling technique was followed to draw samples from all villages in the three blocks. From each stratum, 20% of the villages were selected. In each village, 10% of the households were again selected at random, with individual household being the sampling unit. Results: Availability of in-house toilets in the study area was only 22% with 73% utilization among them. With regard to community toilets, the availability and utility was grossly inadequate. Knowledge about importance of toilet use was more among households with toilets when compared to their counterparts. The knowledge about government giving subsidy to construct toilets was also lacking. Conclusion: The efforts to improve sanitation needs to be sustainable with stress on IEC and community participation.